PERKEMBANGAN JASA TRANSPORTASI PO RUDI DI LEBAK BANTEN TAHUN 1986-1998 (PENGARUH TERHADAP KEHIDUPAN SOSIAL-EKONOMI MASYARAKAT KABUPATEN LEBAK BANTEN) - Ribawati, Eko; Nashar, Nashar; Kirana, Donita (Universitas Indraprasta PGRI, 2020)
This research is to f ind out the history, development and influence of PO Rudi’s transportation service in Lebak Regency in 1986-1998. The problems examinedin this study are about the existence of PO Rudi transportation services in LebakRegency in terms of history starting from the initial history of the establishment,the development of the PO Rudi transportation service company and the influenceon the socio-economic life of the Lebak community. This research study is morefocused in the 1986-1998 timeframe because of the dynamics in thetransportation services company that initially succeeded in being setback. Themethod used in this study is the historical method which includes: Heuristics,Source Critism, Interpretation and Historiography. The results of this studyindicate that the geographical general description of Lebak Regency consistmostly of agricultural areas so that the majorty of the community works asfarmers. Lebak community agricultural output has increased every year so itrequires adequate transportation to sell agricultural products. The distancebetween Lebak Regency and other regencies is quite far, Lebak people usually doactivities using traditional transportation or on foot. This is the background of theestablishment of the PO Rudi transportation service company. PO Rudi’stransportation services company underwent a good development in 1986-1998.In the development of this company had suffered a setback due to the monetary crisis and the development of other public transportation. Evidenced by theincrease in ticket prices and there are people who switch to using othertransportation services such as Mulyawan and Mulyana Jaya in Lebak Regency.But this company is able to survive and maintain its exsistence until now. Thiscompany provides direct and indirect influence on the socio-economic life of thepeople of Lebak Regency. Evidenced by the development of small businessesbecause of the availability of supply of goods from certain regions.Keywords: Transporation Service, PO Rudi, Lebak Regency.